Growth and characterization of large size lead‐free ferroelectric K(Ta, Nb)O3 single crystal. Issue 10 (24th April 2021) - Zhang, Yuanyuan; Li, Shuhuan; Liu, Fengying; Wang, Lihai; Wang, Xuping; Zheng, Limei; Yang, Liekun; Yang, Yuguo; Lv, Xianshun; Yu, Huajian; Liu, Bing; Li, Jing; et al.
Abstract: Lead‐free piezoelectric materials with excellent performance are greatly demanded for the environmental issues. The lead‐free ferroelectric single crystals are therefore greatly concerned for their much higher piezoelectricity than the polycrystalline counterparts and the domain‐tunable property. However, the growth of large size and high‐quality lead‐free ferroelectric crystals has always been a great challenge. In this work, a ferroelectric KTa1‐ x Nb x O3 (KTN) single crystal with an extremely large size of 25 × 25 × 37 mm 3 was grown using the modified top‐seeded solution growth method. The large size enabled us to carry out comprehensive investigations on the crystal. The complete sets of dielectric, piezoelectric, and elastic constants for the [001]C ‐poled KTN crystal with quasi single domain state were determined. Results showed that the crystal exhibits high electromechanical coupling coefficients with k t ~0.642 and k 33 ~0.679. Furthermore, the orientation dependence of the piezoelectric, dielectric, and elastic properties was determined by the tensor matrix transformation technique, and the maximum d 33, s 33 E, and k 33 were found along the polar direction [001]C . This work not only provides important guidance for the growth technology of lead‐free ferroelectric crystals but also offers essential datasets of lead‐free alkali niobate system, which is of great importance for both theoretical studies and designs of electromechanical devices. Abstract : The grown K(Ta, Nb)O3 single crystal and the P‐E hysteresis loops.